Mogućnosti smanjenja potrošnje energije u vuči vlakova - Zavada, Josip (Promet - Traffic&Transportation, 2012)
The paper deals with the possibility of energy consumption reduction in train traction. The mathematical model of train traction calculation is furnished and accommodated for purposes of definition of optimum journeys by the criterion of least energy consumption in given peripheral conditions i.e. within specified operation time and at highest allowed operation speeds. Based upon the model worked out the calculations have been completed on the example of one route section and different types, trains and train masses. The values of absolute and relative deviations in energy consumption have been obtained for different modes of operation and the most favorable methods of operation from the point of energy consumption have been established. In order to have certain optimum aspects of operation carried out in practice the paper puts forward suggestions for the elaboration and form of instructions for the operator. These instructions should for reasons of simplicity and easy reference contain graphical symbols and necessary operation information. It has been suggested to name the manual 'Operator's Information' while it would serve as recommended operation method to the driver. The paper lists all variants and forms of issuance of the proposed operator's information.